Effect of interventions including provision of personalised cancer risk information on accuracy of risk perception and psychological responses: A systematic review and meta-analysis. Issue 1 (January 2020) - Bayne, Max; Fairey, Madi; Silarova, Barbora; Griffin, Simon J.; Sharp, Stephen J.; Klein, William M.P.; Sutton, Stephen; Usher-Smith, Juliet A.
Highlights: Conceptualisation of risk is a complex cognitive process. Individuals tend to overestimate their risk of cancer at baseline. Immediately after risk information over 80% of people are able to recall the number. However, less than half believe that to be their risk, thinking their risk is higher. Risk information has either no effect or reduces worry, anxiety and depression. Abstract: Objective: To synthesize the literature on the effect of provision of personalised cancer risk information to individuals at population level risk on accuracy of risk perception and psychological responses. Methods: A systematic review and random effects meta-analysis of articles published from 01/01/2000 to 01/07/2017. Results: We included 23 studies. Immediately after provision of risk information 87% of individuals were able to recall the absolute risk estimate. Less than half believed that to be their risk, with up to 71% believing their risk to be higher than the estimate. Provision of risk information increased accuracy of perceived absolute risk immediately after risk information compared with no information (pooled RR 4.16 (95%CI 1.28–13.49), 3 studies). There was no significant effect on comparative risk accuracy (pooled RR 1.39 (0.72–2.69), 2 studies) and either no change or a reduction in cancer worry, anxiety and fear. Conclusion: These findings highlight the complex cognitive processes involved in the conceptualisation of risk. Practice implications: Individuals who appear to understand and are able to recall risk information most likely do not believe it reflects their own risk.